MEDICATION SYSTEM ANALYSIS OF AN UNIVERSITY HOSPITAL IN THE STATE OF GOIÁS - Ana Elisa Bauer de Camargo Silva (Universidade Federal de Goias, 2004)
The medication errors can bring serious consequences to patients, professionals andhealthcare institutions, they have multiple causes, amongst them failures related to theprofessionals and related to the medication system. This studys objective was to identify and toanalyse the medication system process, its failures in order to propose improvement actions to thehospital. This exploratory descriptive study took place in the medical clinical unit and in thepharmacy of a general and university hospital of the state of Goiás, after approval of theCommittee of the Ethics of the correspondent hospital. The sample included: (first phase) apharmacist, (third phase) 40 professionals divided into 12 resident physicians (30%), 20 nursingprofessionals (50%), 8 pharmacy team members (20%); 294 patient charts were also used. Thedata was collected in 2002 and consisted of an interview with the professional in charge of themedication system, and non-participant observation of the environment and actions of theprofessionals and the academic people, interviews with the professionals and patient chartanalysis. The professionals were asked to sign on the Free Will Participation Agreement. It waspossible based on the data collected to describe the following processes: handwriting medicationprescription using carbon paper, individually dose dispensing and that the nursing professional whoadministrates the drug is not the same that prepares it in the clinical unit. The results based on the21 days of observation of the drug prescription, dispensing and administration processes were: theenvironment is the main problem in the prescription (75%) and dispensing (30,6%) processes, it isa noisy place and interruptions frequently occur; safety failures during the technique and inadvancedrug preparation appeared in the top (46,8%) in the preparation process. The datacollection also allowed to build a chart of the 60 steps from drug prescription to monitoring. Theresults from the interviews showed that the most frequent errors were related to both prescription(29%) and schedule (20,6%) and their main cause were individual failures and lack of attention(47,7%) and work overload (14,5%). The individual failures were also listed as the main failure inthe medication system (27%). In order to avoid errors 28,3% of the answers suggested to changethe individuals behavior, and orientation as the administrative action more frequently taken (25%).The patient chart analysis found out the following drug prescriptions characteristics: 64,6%readable, 62,2% using drug brand names as well as the active principle name, 95% incomplete formissing information, 96% using abbreviations and 30% with erasures. Concerning to drugnotifications, the analysis also found out 7 nursing reports, one from the physician and that there isno error report in the clinical unit. The suggested improvements to avoid errors and enhance thesystem are: computerized physician order electronic entry, unit dose, errors reports, non-punitiveapproach, patient safety, and at last to make the system as simple and lean as possible.